Respon Mahasiswa terhadap Penggunaan Bahan Ajar Kajian Fiksi Berbasis Kearifan Lokal - Simarmata, Mai Yuliastri; Sulastri, Saptiana; Hartati, Mesterianti (STKIP PGRI Bandar Lampung, 2020)
Fun learning is learning that is carried out interactively, fun, challenges, and motivates students to participate actively. Therefore, the development of teaching materials can motivate students to be more active in the learning process. The use of teaching materials used by students in reality is still minimal. Therefore, this study aims to describe and analyze student responses to the use of local wisdom-based study of fiction teaching materials. This research uses the Research and Development (RnD) type of research. Research respondents were 44 students who took the subject of fiction study in the even semester of the 2019/2020 school year. Data collection techniques using student response questionnaires, observation and documentation. Data analysis techniques using percentages. The results of the research on student responses to the use of fiction study teaching materials were 83.8% and were in the feasible category with a very good predicate. Based on student responses It can be said that students as users of teaching materials give good responses to the Fiction Study textbook. Thus the use of teaching materials can increase student learning motivation.